The Application of Quality Function Deployment in Car Seat Industry - Humiras Hardi Purba; Sunadi Sunadi; Suhendra Suhendra; Else Paulina (ComTech: Computer, Mathematics and Engineering Applications, 2020)
The research aimed to ensure the right design of new products based on customer needs and to improve competitiveness based on renewal marketing strategies and customer needs in the car seat industry. Customer satisfaction ratings were used to compare with competitors. Then, the Quality Function Deployment (QFD) was implemented for the analysis. The research used total sampling or complete enumeration. So, the sample size was the same as the population size. Based on calculations using the QFD method, it shows that the seat option has the highest percentage of technical requirements in the car seat industry around 27,39%. The second factor is material about 25,94%, and the third factor is the damping characteristic about 19,17%. For continuous quality improvement in the future, a lot of customer needs regarding the seat car need to be developed.